Evaluation of factors influencing the quality of life of residents living close to Northwest Solid Waste Treatment Complex Cu Chi districts, Ho Chi Minh City - Mai, Le Thi Tuyet; Chau, Nguyen Lam Hong; Thao, Do Phuong; Anh, Hoang (IOP conference series. Earth and environmental science, 2024)
Ho Chi Minh City (HCMC) grapples with a significant surge in waste generation, a consequence of urban expansion and development. The escalating waste poses a threat to the well-being of residents, particularly those in proximity to waste treatment facilities. This study delves into the impact of the Northwest Solid Waste Treatment Complex (NSWTC), a key waste treatment facility in HCMC, on residents residing in its immediate vicinity. The assessment encompasses 120 subjects living within a semi-permanent radius of 5 km from NSWTC. The residents’ Quality of Life (QoL) is quantitatively evaluated using the WHO QoL assessment scale (WHOQOL-BREF), comprising 26 survey questions categorized into four domains: living environment, physical health, psychological well-being, and socio-economic conditions. The identification of these domains is facilitated through bivariate and multivariate logistic analyses. Utilizing SPSS 20.0 software for data analysis, the findings reveal that a noteworthy 76.7% of subjects exhibit a subpar QoL. The overall QoL score, averaging 49.08 ± 18.82, falls considerably below acceptable standards, attributing this decline to environmental factors such as odours, dust, falling waste, water quality, and socio-economic conditions.